Risk factors for overweight and obesity in pre-school children - Polak, Ewelina; Dereń, Katarzyna; Łuszczki, Edyta; Wyszyńska, Justyna; Piątek, Adriana; Mazur, Artur (European Journal of Clinical and Experimental Medicine, 2018)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Obesity in children and adolescents is a growing problem in the 21st century. The epidemic of chronic non-communicable diseases resulting from obesity is currently one of the biggest problems of modern medicine. Excessive body weight is the result of a long-lasting imbalance between the amount of energy supplied and its expenditure. Energy regulation of the body is subject to both genetic and environmental factors. Among other things, due to this, the problem of excessive body weight is most severe in societies with a high degree of socio-economic development. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. The aim of this paper is to determine the influence of selected environmental and social factors on the occurrence of overweight and obesity in pre-school children. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The study included pre-school children from south-eastern Poland. After obtaining the consent from parents, 200 children (87 boys, 113 girls) aged 3 to 6 years were examined. A questionnaire used for the research was derived from the program: European Pilot Study Evaluating the Influence of Local Promotional Activities on Prevention of Obesity in Pre-school Children. In the subjects, body weight was measured on an electronic scale three times and the body height was measured three times using a stadiometer. Obesity was determined according to the criteria developed by the International Obesity Task Force (IOTF). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The prevalence of overweight and obesity among children amounted to 6.4% in 3-year-olds, 11.3% in 4-year-olds, 17.7% in 5-year-olds, and 20.7% in 6-year-olds. A factor significantly increasing the risk of obesity among the examined girls and boys was the mother’s BMI index. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Although knowledge about the factors that promote overweight and obesity is common, it is still a common health problem. Particular attention should be paid to the prevention of obesity in children of parents with a BMI above 30 kg/m2 . Early maternal education can change the lifestyle of the whole family.